Virtual Training Module for the Production of Rubber Adhesives Through the Production of Cyclopentenol - Garcia Almache, Brayan Abelardo (2023)
This article developed a didactic module that presents the evolution of the process of a Perfectly Agitated Reactor to obtain Cyclopentenol, which is used for the production of rubber adhesives. For this process was implemented con- trollers such as: Numerical Methods, Fuzzy and MPC. The mathematical model of the process as well as the control algorithms are implemented on the Raspberry Pi board which is embedded in the module. The module has connectivity with a computer in which it has a virtual environment that resembles an industrial pro- cess which was developed in Unity 3D, the same environment is interactive and immersive for anyone interested in the area of control and virtualization. The vir- tual environment simulates the process through animations allowing to visualize a process as if it were real showing elements such as: SCADA systems for the con- trol room, industrial instrumentation in the process lines, catastrophic eventswhen an error occurs, sounds of an industrial environment, etc. Finally, the evaluation of each of the controllers implemented in the process was verified.